High-Throughput Screening and Characterization of a High-Density Soybean Mutant Library Elucidate the Biosynthesis Pathway of Triterpenoid Saponins. (12th February 2019) - Krishnamurthy, Panneerselvam; Fujisawa, Yukiko; Takahashi, Yuya; Abe, Hanako; Yamane, Kentaro; Mukaiyama, Kyosuke; Son, Hae-Reon; Hiraga, Susumu; Kaga, Akito; Anai, Toyoaki; Tsukamoto, Chigen; Ishimoto, Masao
Abstract: Triterpenes (C30 ) constitute one of the diverse class of natural products with potential applications in food, cosmetic and pharmaceutical industries. Soyasaponins are oleanane-type triterpenoids widespread among legumes and particularly abundant in soybean seeds. They have associated with various pharmacological implications and undesirable taste properties of soybean-based food products. Uncovering the biosynthetic genes of soyasaponins will provide new opportunities to control the pathway for human benefits. However, the pathway of soyasaponin biosynthesis has not been fully elucidated in part because of a paucity of natural mutants. Here, we applied a structured high-density soybean mutant library for the forward genetic screening of triterpenoid biosynthesis. The seed soyasaponin polymorphism in the mutant library was evaluated using a high-throughput thin-layer chromatography and liquid chromatography tandem mass spectrometry analysis. This screening identified 35 mutants (3.85% of 909 mutant lines) with seven unusual soyasaponin phenotypes (Categories 1–7), which was greater than the number of natural mutants reported previously (22 mutants, 0.18% of ∼12, 428 accessions). Nine unique intermediates of soyasaponin biosynthesis were identified and their chemical structures were estimated based on their MS/MS fragment patterns. Based on published information, 19 mutants could be associated with loss of function of four individual soyasaponin biosynthesis genes identified through expressed sequence tag mining or positional cloning, whereas the remaining 16 mutants were novel and may facilitate discovery of the unknown biosynthetic genes of soyasaponins. Our approach and library may help to identify new phenotype materials and causative genes associated with specialized metabolite production and other traits.